Gāyatrī mantra āṇi upāsanā - Devadhara, Sa. Kr., 1926- (Prasāda Prakāśana, 1978)
On the significance of the daily ritual of Brahmins (sandhyā) and the Vedic hymn to the Sun god (Gāyatrī); traditional exposition based on allied texts.